PROSES PEMBELAJARAN VOKAL GRUP: DALAM UPAYA MENINGKATKAN TEKNIK VOKAL PADA KEGIATAN EKSTRAKURIKULER DI SMPN 8 DENPASAR - Gandu, Maria Fransiska; Sumerjana, Ketut; Laksmi, Desak Made Suarti (MELODIOUS : JOURNAL OF MUSIC, 2024)
Implementation of the MBKM curriculum must be developed by each university and study program. SMP Negri 8 Denpasar was founded in 2006 as an effort to make Denpasar a city of educators as well as responding to the development of the city of Denpasar. SMP Negeri 8 Denpasar is a state junior high school that serves junior high school education in Denpasar City. The lessons provided include all mandatory subjects according to the applicable curriculum. SMP Negeri 8 Denpasar has teaching staff who are competent in their subject areas so they are of high quality and are one of the best in Denpasar City. There are also various school facilities such as comfortable classrooms, libraries, sports fields, canteens and others. Therefore, researchers are interested in carrying out the MBKM program required by the campus in the form of Teaching Assistance activities in the Education unit to gain experience in the field as a teacher. Preparing a thesis using syntax and cooperative methods using scientific principles which contains a series of stages, namely the preparation stage, the presentation stage, the training stage (practice), and the performance stage. The learning process includes activities from opening the lesson to closing the lesson. The initial activity is to provide a general overview of the material that the author will provide to students. The activities at the end of the lesson are summarizing the learning results and giving appreciation or appreciation to students. Group vocal learning and vocal techniques at this school use the demonstration method and lecture method. This aims to apply new methods to make music learning at SMPN 8 Denpasar more effective.